2020
DOI: 10.21203/rs.3.rs-15576/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Presentation Intervals and the Impact of Delay on Breast Cancer Progression in a Black African Population.

Abstract: BACKGROUND: The help-seeking interval or the primary-care interval are points of delays in breast cancer presentation. To inform future breast cancer down-staging intervention, we described the contribution of each interval to the delay and the impact of delay on tumor progression.METHOD: Multicentered survey from June 2017 to May 2018. We hypothesized that most patients visited the First Healthcare Provider within 60days of tumor detection. Inferential statistics were by t-test, chi-square test, and Wilcoxon-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…6,[17][18][19][20] Studies have reported that the delays for patients with breast cancer in Africa range from 4 months to 17 months; our study falls in the middle of this range at nearly 10 months. 21 Delays in cancer diagnosis may lead to more advanced disease at presentation and increased mortality. This has been most widely studied in breast cancer; delays over 12 weeks are correlated with worse 5year survival in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…6,[17][18][19][20] Studies have reported that the delays for patients with breast cancer in Africa range from 4 months to 17 months; our study falls in the middle of this range at nearly 10 months. 21 Delays in cancer diagnosis may lead to more advanced disease at presentation and increased mortality. This has been most widely studied in breast cancer; delays over 12 weeks are correlated with worse 5year survival in breast cancer.…”
Section: Discussionmentioning
confidence: 99%